A CO2-tolerant nanostructured layer for oxygen transport membranes - Zhang, Z.; Chen, D.; Gao, Y.; Yang, G.; Dong, F.; Chen, C.; Ciucci, F.; Shao, Zongping (Royal Society of Chemistry, 2014)
Dual-layer membranes with enhanced CO2 tolerance and unprecedented oxygen permeability under CO2-containing sweep gas are reported. Specifically, a SrFe0.8Nb0.2O 3-d/Ba0.5Sr0.5Co0.8Fe 0.2O3-d (SFN/BSCF) dual-layer membrane structure has been successfully prepared by pulsed laser deposition of SFN thin layer onto polished BSCF membranes. The phase structure and microstructure of the SFN/BSCF membrane are characterized by XRD and TEM, respectively. Two distinct phases originated from SFN and BSCF are both obtained, which suggests that the SFN is in high crystallinity under the as-deposited condition and BSCF maintains its original status. TEM images clearly show that SFN nanostructured layer is compactly coating on the BSCF substrate. Oxygen permeation fluxes of 2.721, 2.276, 1.809 and 1.303 mL cm-2 min-1 at 900, 850, 800 and 750 °C are attained for a ~45 nm nanostructured SFN layer decorated on a 1 mm thick BSCF membrane using air as the feed and He as the sweep gas. These high oxygen permeation fluxes are comparable with the pristine BSCF membrane since SFN membrane is also a promising mixed conductor and the coated layer is extremely thin. Under He sweep gas with 10% CO2, a stable oxygen permeation flux of ~2.25 mL cm-2 min-1 at 850 °C is maintained for ~550 min with the SFN/BSCF membrane, while it is only lower than 0.4 mL cm-2 min-1 with the uncoated membrane. The results indicate that both high oxygen flux and stability can be simultaneously achieved with adoption a nanostructured protective layer. © the Partner Organisations 2014.